Itch.io and the One-Dollar-Game: How Distribution Platforms Affect the Ontology of (Games as) a Medium - Werning, Stefan; Justus Liebig University Giessen (My University, 2019)
The article at hand outlines formal and media ontological implications of digital distribution by analyzing how independent game publishing platform Itch.io enabled the one-dollar game as an emergent form of cultural expression. Production studies, particularly with reference to film, have investigated how new modes of production have shaped emergent genres and forms like chase scenes and location shooting; this article makes a similar case for distribution modalities. For that purpose, studies and creators accounts on the distribution of literature (Carr, 2015), film (Meusy, 2002) and music (Anderton 2019) are adapted. Characteristic software affordances of Itch.io are analyzed to determine how the platform frames the selling and advertising of disposable games. A corpus of almost 300 one-dollar games was compiled by scraping the Itch.io website. Through a comparative content analysis, several unique microgenres, most of which can only feasibly exist within this product category, as well as performative and simulational aspects of game publishing are studied. The findings are related to ongoing debates about the ontology of (digital) games, thereby connecting the material-semiotic notion of platformization (Helmond, 2015) to cultural production.
Keywords: game distribution; media ontology; platformization; comparative content analysis; soft-ware affordances; ddc:300